2019
DOI: 10.1002/ldr.3378
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cropping of soybean alters the bulk and rhizospheric soil fungal communities in a Mollisol of Northeast PR China

Abstract: Continuous cropping of soybean causes soil degradation and decreased soybean yield in Northeast PR China. However, the mechanism underlying the effect on soil fungal communities and the relationship between these effects and cropping systems have not yet been fully elucidated. In this study, we comparatively investigated the abundance, diversity, and structures of fungal communities in the bulk and rhizospheric soils of soybean grown in two cropping systems, that is, continuous cropping (CC) of soybean and cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 68 publications
(122 reference statements)
3
40
1
Order By: Relevance
“…The dominant genus Pseudombrophila in T5 (14.3%) became one of the least abundant genera in T30 (1.5%). These observed differences in different groups further support previous reports demonstrating that the abundance and structure of fungal communities are highly influenced by continuous cropping [11][12][13][14].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The dominant genus Pseudombrophila in T5 (14.3%) became one of the least abundant genera in T30 (1.5%). These observed differences in different groups further support previous reports demonstrating that the abundance and structure of fungal communities are highly influenced by continuous cropping [11][12][13][14].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies on soybean, ginger, potato, cucumber, and cotton have found that the alpha diversity of bacteria and fungi was decreased due to continuous cropping year, and the soil microbial metabolic diversity and soil physicochemical properties were also significantly affected [10][11][12][13]. The relative abundance of pathogenic fungi in rhizospheric soil was revealed to be significantly higher in continuous cropping than in cropping rotation systems [14]. However, the mechanism underlying the effect on soil microbial communities and the relationship between these effects and continuous cropping systems have not yet been fully elucidated for sugar beet.…”
Section: Introductionmentioning
confidence: 82%
“…Likewise, Fusarium oxysporum and Fusarium solani cause root rot and wilt, collar canker, and dieback disease in tea plants [45,46]. Recent studies show that continuous planting of strawberry and soybean leads to an increase in the relative abundance of Fusarium oxysporum [53,54]. In this study, Fusarium (Fusarium oxysporum, Fusarium solani) and Microidium phyllanthi produced the same result as in a previous study in response to tea monoculture, suggesting that continuous tea cropping may increase the occurrence of pathogenic fungi in soils.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cropping of soybean increased the relative abundance of Fusarium oxysporum in soil 6 , and…”
Section: Discussionmentioning
confidence: 99%
“…Continuous cropping, which is the agricultural practice of long-term cultivation of the same crop in identical soil, is a vital agricultural issue because it leads to reduced the soil quality and augmentation of harmful pests and soilborne microbial communities, resulting in yield decline of plants 1 . Rhizosphere soil microorganisms affect the growth, development, and health status of plants 2 , and the in uences of continuous cropping on microbial community structures in rhizosphere soil have gained considerable attention [3][4][5][6][7] . When compared with bacteria, rhizosphere fungi are important decomposers that play vital roles in balancing the rhizosphere ecosystem 8 .…”
Section: Introductionmentioning
confidence: 99%